Structural vibration control by shape memory alloy damper. - Han, Yu-Lin
A damper device based on shape memory alloy (SMA) wires is developed for structural control implementation. The design procedures of the SMA damper are presented. As a case study, eight such SMA dampers are installed ina frame structure to verify the effectiveness of the damper devices. Experimental results show that vibration decay of the SMA damper controlled frame is much faster than that of the uncontrolled frame. The finite element method is adopted to conduct the free and forced vibration analysis of the controlled and uncontrolled frame. The experimental and numerical results illustrate that the developed SMA dampers are very effective in reducing structural response and have great potential for use as efficient energy dissipation devices with the advantages of good control of force and no lifetime limits, etc.
Keywords: Shape memory alloy (SMA).; Smart material; Damper; Structural control; Vibration; Earthquake; Frame structure